2010
DOI: 10.1371/journal.pone.0014190
|View full text |Cite
|
Sign up to set email alerts
|

Do Gene Variants Influencing Adult Adiposity Affect Birth Weight? A Population-Based Study of 24 Loci in 4,744 Danish Individuals

Abstract: BackgroundSeveral obesity risk alleles affecting adult adiposity have been identified by the recent wave of genome wide association studies. We aimed to examine the potential effect of these variants on fetal body composition by investigating the variants in relation to birth weight and ponderal index of the newborn.Methodology/Principal FindingsMidwife records from the Danish State Archives provided information on mother's age, parity, as well as birth weight, birth length and prematurity of the newborn in 4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Sovio et al (2011), for example, found that genetic variants associated with increasing obesity risk at the FTO locus were associated with earlier adiposity rebound (but not with earlier Age Peak ). Andersson et al (2010) found lower BMI Peak in individuals carrying the FTO risk genotype at rs9939609 (AA), but higher BMI later in childhood, again showing that there are complex age-dependent variations in genetic control of BMI, with lower infant BMI being characteristic of individuals at ultimately higher risk of obesity. Our results emphasize the point that while environmental factors are very important in shaping the infant BMI-for-age curve (as shown by the secular trends analysis), the majority of inter-individual variation is nonetheless attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sovio et al (2011), for example, found that genetic variants associated with increasing obesity risk at the FTO locus were associated with earlier adiposity rebound (but not with earlier Age Peak ). Andersson et al (2010) found lower BMI Peak in individuals carrying the FTO risk genotype at rs9939609 (AA), but higher BMI later in childhood, again showing that there are complex age-dependent variations in genetic control of BMI, with lower infant BMI being characteristic of individuals at ultimately higher risk of obesity. Our results emphasize the point that while environmental factors are very important in shaping the infant BMI-for-age curve (as shown by the secular trends analysis), the majority of inter-individual variation is nonetheless attributable to genetic factors.…”
Section: Discussionmentioning
confidence: 92%
“…Given this, the infant BMI peak may be a useful trait for genetic analysis; known genetic variants associated with BMI and obesity in adults tend to associate fairly weakly with birth weight and ponderal index (Andersson et al, 2010) and with later infancy BMI (Choh et al, 2011). In contrast, a recent study using curve fitting to derive Age Peak and BMI Peak found significantly lower BMI Peak in carriers of a high risk genotype for the obesity gene FTO (Sovio et al, 2011).…”
mentioning
confidence: 99%
“…This finding is in accordance with other studies. 17,30,32,35,36 Elks et al report a marginal positive correlation of birth weight to the obesity-risk-allele-score, but the correlation was significantly more robust after the first 6 weeks of life. 37 The FTO and MC4R risk alleles are thought to contribute to BMI increase through regulation of central nervous system messages to the hypothalamus, regulating appetite, satiety and calorie-dense preferences.…”
Section: Discussionmentioning
confidence: 99%
“…While there was no significant difference in the effect sizes observed in adults and children, the effects observed for the loci in or near SEC16B , TMEM18 and KCTD15 tended to be larger in children than in adults, whereas the opposite was observed for the BDNF locus. Of interest is that there is currently no evidence that any of the established BMI loci are associated with birth weight [85,86]. …”
Section: Genetic Associations In Children and Adolescentsmentioning
confidence: 99%